P-200 YI Multi-disciplinary Management of Complex Upper Gastrointestinal Crohn's Disease in a Teenager. (March 2016) - Siva, Shivi; Rubin, David; Dachman, Abraham; Kahn, Stacy
Abstract : Background: Although upper Gastrointestinal Crohn's Disease (UGCD) is uncommon and often asymptomatic, an unusual aggressive variant may lead to nutritional risk and debilitation. We describe the management of a teenager with UGCD manifesting as multiple and recurrent strictures of duodenum and jejunum resulting in malnutrition and weight loss. Methods: A 17 year-old male with ileal and gastric Crohn's disease diagnosed at age 6 was evaluated for new symptoms of persistent nausea and weight loss. Prior treatments included steroids, 6-mercaptopruine, infliximab and endoscopic dilatation for an antral stricture. He was presently on adalimumab 40 mg and methotrexate 25 mg weekly. Physical examination was remarkable for epigastric and bilateral abdominal tenderness. Barium upper GI (UGI) series revealed 3 high-grade strictures in the duodenal sweep and jejunum. He underwent stricturoplasty of these strictures. Post-operatively he was started on methotrexate, esomeprazole and adalimumab was increased to 80 mg/40 mg weekly, with moderate symptom improvement. Within 5 months, his symptoms recurred. Repeat UGI series revealed a partially obstructive, focal circumferential stricture of the mid jejunum. Exploratory laparotomy and Heineke-Mikulicz stricturoplasty were performed. Exclusive enteral nutrition (EEN) therapy was recommended on multiple occasions but the patient declined. Within 5 months he again presented with symptom recurrence. Repeat evaluation confirmed 2 new short segment areas with focal narrowing in the proximal post-anastomotic jejunum. Medical management was optimized by confirming detectable adalimumab levels within range associated with response at 18 μg/mL. Ultimately, he required bypass gastro-jejunostomy. Post-operative therapy was vedolizumab combined with 6-MP and esomeprazole. At 6 months, he is in clinical remission and has gained 15 pounds. He receives ongoing monitoring of disease activity with regular endoscopic surveillance and clinical follow-up. Results: N/A Conclusions: Gastro-duodenal involvement occurs in 0.5% to 4% of patients with CD. 1–4 Isolated stomach and duodenum disease accounts for less than 0.07% of all cases of CD. 5 Prevalence remains at 0.5% to 13% based on retrospective studies. Most patients remain asymptomatic. 6 Symptomatic GDCD occurs in approximately 5.5% 7 and is characterized by nausea, vomiting 8 and epigastric pain not relieved antacids or food intake. 4 Teenagers suffer from more severe disease compared to adults. 9 Medical treatments include proton pump inhibitors for symptom relief. Steroids may be beneficial for non-obstructing disease and 6-mercaptopurine/azathioprine has shown steroid sparing effect. 10 No data exist on the effectiveness of mesalamine or methotrexate. Efficacy of Anti-TNFα needs to be proven yet. 11 Endoscopic balloon dilatation is best for single, short and moderately thick stricture. 12 Strictures in the 2nd or 3rd part of duodenum are often amenable to stricturoplasty while By-Pass Surgery 13 is better for multiple strictures in the 1st or 4th parts of duodenum. EEN is effective 14 in inducing remission in active CD equivalent to steroids. 15 GDCD is usually asymptomatic and uncommon with little data to guide medical therapy. Multiple surgical options exist based on location and extent of disease and availability of local expertise. It's imperative for clinicians to exercise a vigilant approach to change in symptoms in patients with GDCD. Imaging, surveillance, endoscopy and escalation of therapy can prevent debilitation and further disease progression.